Identifikasi Cemaran Escherichia Coli Pada Makanan Jajanan yang Dijual di Kampus Universitas Abdurrab - Asiska Permata Dewi; Reza Irma (Journal of Pharmaceutical and Sciences, 2023)
Snack food is the food processed and sold as ready-to-eat food. The snack food presented must notice sanitation and hygiene so that the food quality remains. This research aimed to identify the contamination of Eschericia Coli bacteria on snack food sold at Abdurrab University Campus. Eschericia Coli bacteria was used as an indicator of microbiological contamination on food. E. coli bacteria was non-pathogenic when it is in the digestive system and becoming pathogenic when it is outside the digestive sistem. The method used was culture method or bacteria breeding in enrichment media (Brain Hearth Infosion Broth), gram coloring, testing on selective media (Eosin Metilen Blue Agar) and test of biochemical reaction (Sulfur Indol Motility Media, Voges Pakauser, Metyl Red, Simon Citrat). The testing result on BHI broth media, 5 to 10 positive samples containing bacteria continued by gram coloring test. In the gram coloring pink color was formed which indicated that the sample contained negative gram bacteria. The test on selective media and biochemical reaction did not show the traits of Eschericia coli bacteria. Thereby, 10 types of snack food tested were not contaminated by Eschericia coli bacteria.